2022
DOI: 10.1002/pbc.30071
|View full text |Cite
|
Sign up to set email alerts
|

Ocular survival after intra‐arterial chemotherapy for retinoblastoma improves with accrual of experience and programmatic evolution

Abstract: Background: Intra-arterial chemotherapy (IAC) for the treatment of intraocular retinoblastoma has gained recognition as a method to improve ocular salvage; however, there is a paucity of evidence supporting treatment factors prognosticating ocular survival. Methods: All patients with retinoblastoma treated with IAC at a single institution between December 2008 and December 2019 were evaluated. Patient demographics, tumor classification, prior treatments, procedural data, other non-IAC therapies, adverse reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…This highlights the importance of limiting the delivery of this complex treatment in high‐volume centers with technical expertise. Retinoblastoma is a rare disease and one individual institution will not see a substantial number of patients to acquire the required experience with the delivery technique in a short period of time; extensive training and programmatic focus are needed for success 29 . This study was initiated in 2014 and therefore the results reported here need to be interpreted in its due historical context as one can expect greater experience with IA therapy at the current time.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of limiting the delivery of this complex treatment in high‐volume centers with technical expertise. Retinoblastoma is a rare disease and one individual institution will not see a substantial number of patients to acquire the required experience with the delivery technique in a short period of time; extensive training and programmatic focus are needed for success 29 . This study was initiated in 2014 and therefore the results reported here need to be interpreted in its due historical context as one can expect greater experience with IA therapy at the current time.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment Treatment modalities for Rb have changed rapidly over the past decade [40] . and the survival of many Rb cases that used to die in the past has improved in recent years [3,[57][58][59] . In general, the available treatment options for Rb include surgery (including enucleation and pars plana vitrectomy); focal therapies (including cryotherapy, laser photocoagulation, and transpupillary thermotherapy); chemotherapy (including intravenous chemotherapy, intra-arterial chemotherapy, and intravitreal chemotherapy), and radiotherapy (including plaque brachytherapy and external beam technique) [16] .…”
Section: Rb Prognosis and Screeningmentioning
confidence: 99%